2018
DOI: 10.1055/s-0039-1681089
|View full text |Cite|
|
Sign up to set email alerts
|

Prehospital Telemedical Emergency Management of Severely Injured Trauma Patients

Abstract: Background Trauma is a global burden. Emergency medical services (EMS) provide care for individuals who have serious injuries or suffered a major trauma. Objective This paper provides a comprehensive overview of telemedicine applications in prehospital trauma care. Methods We conducted a systematic review according to PRISMA guidelines. We identified articles by electronic database search (PubMed, EMBASE, the Cochrane Library, CINAHL, SpringerLink, LIVIVO, DARE, IEEE Xplore, Google Scho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 90 publications
0
11
0
1
Order By: Relevance
“…Two narrative synthesis reviews looked at the role of telehealth in the management of trauma patients. 52,53 The more recent review focused specifically on pre-hospital trauma care. 52 The authors identified telemedical assistance by real-time telemetry and telemedical pre-hospital notification as complementary applications of the technology but concluded that evidence of effectiveness in this setting remains limited.…”
Section: Trauma Reviewsmentioning
confidence: 99%
See 1 more Smart Citation
“…Two narrative synthesis reviews looked at the role of telehealth in the management of trauma patients. 52,53 The more recent review focused specifically on pre-hospital trauma care. 52 The authors identified telemedical assistance by real-time telemetry and telemedical pre-hospital notification as complementary applications of the technology but concluded that evidence of effectiveness in this setting remains limited.…”
Section: Trauma Reviewsmentioning
confidence: 99%
“…55 The use of telehealth in ambulances allows service models based on early initiation of diagnosis and/or treatment by paramedics as well as triage to divert less seriously ill patients away from EDs when clinically appropriate. 52,58,59 However, barriers remain to the widespread adoption of telehealth technology in some settings. Other mitigation interventions, including improved co-ordination between services, 46 are discussed in the relevant sections of Chapter 3 (see Mitigation studies).…”
Section: Implications For Service Deliverymentioning
confidence: 99%
“…Successful telemedical approaches already exist in the preclinical care of severely injured people [ 17 , 18 ]. A national program for telemedicine consultation after neurotrauma could eliminate the need for 68% of patient transfers [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…This systematic review examined whether clinical decisions are associated with telemedicine use in a prehospital emergency medical setting. To date, feasibility studies, simulated randomized controlled trials [9,26], and systematic reviews [30,32,42] on telemedicine fail to adequately address the role of decision making in patient outcomes. It is difficult to access information on (1) how telemedicine has been implemented and if any protocols exist and (2) measurements of clinical outcomes before versus after telemedicine implementation.…”
Section: Discussionmentioning
confidence: 99%
“…Simulation trials have previously been included in systematic reviews on telemedicine applications in a prehospital setting [30][31][32][33]. This systematic review intended to examine telemedicine use in real-life scenarios to better understand its clinical value and limitations, as it is yet to be embedded into widespread routine use.…”
Section: Study Selectionmentioning
confidence: 99%